Performance Assessment of Crisis Management Plans with the Contribution of Multi-agent Systems - D. Lachtar; E. Garbolino (Chemical Engineering Transactions, 2012)
Crisis management aims to implement precautions of anticipation, vigilance and intervention to meet the targets. It is based on a specific tool called “crisis cell” also based on Crisis Management Plans. Crisis Management Plans are formalized in order to provide to the organizations a structured tool, where the staff involved into the crisis cell can find information and procedures. Usually, the Crisis Management Plans are tested with the preparation of exercises that can involve the Industries, the Civil Protection and the Municipalities. The improvements of these plans are based on the feedback experience from real or simulated events. However, the study of feedback experience according to real crisis show these plans do not guarantee an optimal performance of crisis cells and crisis management process. Crisis cells may become particularly weak and unable to fulfil their missions according to their own points of vulnerability. This fact underlines the importance of the implementation of a comprehensive approach for decision making, particularly on indicators performance ensuring an effective management of emergencies in terms of space and time. In this context, the authors aim to assess the organizational performance of a crisis cell, which can be considered as a complex system. This performance is based on the four main factors that must be assessed: i) The organizational and institutional factors: the complexity of the organizational network ii) The technical and resource factors: the type of infrastructure dedicated to crisis management iii) The time factors iv) The knowledge and skill factors: past experience crises, the level of preparation, the inability to effectively use the alert and communication equipments. The methodology developed is primarily based on systems thinking. The systemic approach aims to understand and simulate the operations of the crisis management, including the interactions between actors which are complex. This model describes the functions and resources of communal safeguard plan. It represents an approach particularly suited to understand the behaviour of a system. This model is also applied to give a formal reflection frame in order to analyze the potential failures of the crisis cell. The proposed methodology includes five steps: systemic exploration, qualitative modelling, dynamic modelling, simulation and risk analysis. This methodology was chosen for several reasons. Firstly, systemic exploration and qualitative modelling aim to understand and to analyze the complexity of a system, set goals and avoid mistakes in decision-making. UML (Unified Modelling Language) will be used to modelling the crisis cell. Secondly, a system to be effective, must know how to react in the time and in the complexity. Dynamic modelling is used to model and simulate the system to deal with the unexpected. MAS (Multi Agent System) were chosen to modelling dynamically the system. This analysis will propose recommendations to the studied organization for improving the organizational structure of the crisis. This methodology is a decision support toolbox that can be used to help the managerial decisions and / or guide decision-making processes in organized systems.